Analisis Keperluan Pembangunan Bahasa Isyarat Malaysia Bagi Terminologi Ibadah - Siti Ramna Khamaruddin; Nurul Asiah Fasehah Muhamad; Norakyairee Mohd. Raus; Adnan Mohamed Yusoff; Mahyuddin Hashim; Noornajihan Ja‘afar; Mohd Nur Adzam Rasdi (Zes Rokman Resources, 2024)
Non-Indexed Publication